Methylglyoxal Has Different Impacts on the Fungistatic Roles of Ammonia and Benzaldehyde, and Lactoylglutathione Lyase Is Necessary for the Resistance of Arthrobotrys oligospora to Soil Fungistasis - Long, Xi; He, Nian-Min; Tan, Li-Xue; Yang, Yun-He; Zhou, Jia-Peng; Liu, Zi-Yi; Mo, Ming-He; Liu, Tong (Frontiers in Cellular and Infection Microbiology, 2021)
Biocontrol of root-knot nematode has attracted increasing attention over the past two decades. The inconsistent field performance of biocontrol agents, which is caused by soil fungistasis, often restricts their commercial application. There is still a lack of research on the genes involved in biocontrol fungi response to soil fungistasis, which is important for optimizing practical applications of biocontrol fungi. In this study, the lactoylglutathione lyase-encoding AOL_s00004g335 in the nematophagous fungi Arthrobotrys oligospora was knocked out, and three mutant strains were obtained. The hyphal growth of mutants on the three media was almost the same as that of the wild-type strain, but mutants had slightly higher resistance to NaCl, SDS, and H2O2. Methylglyoxal (MG) significantly increased the resistance of A. oligospora to ammonia, but decreased the resistance to benzaldehyde. Furthermore, the resistance of the mutants to soil fungistasis was largely weakened and MG could not increase the resistance of A. oligospora to soil fungistasis. Our results revealed that MG has different effects on the fungistatic roles of ammonia and benzaldehyde and that lactoylglutathione lyase is very important for A. oligospora to resist soil fungistasis.